Sen Azrila ; Austeria - Stryjkowski, Julian; Stryjkowski, Julian (Warszawa : Panstwowy Instytut Wydawniczy, 1995)
Two novels depicting the lives of Jews and their customs.
Keywords: Jews -- Poland -- Fiction